The quotable Thoreau - Thoreau, Henry David, 1817-1862 (Princeton University Press, 2011)
This book is a collection of Henry David Thoreau quotations. It features more than 2,000 passages from this iconoclastic American author, social reformer, environmentalist, and self-reliant thinker.